CLINICAL AND BIOCHEMICAL EVALUATION OF THYROID DYSFUNCTION IN ELDERLY: A RELATIONSHIP BETWEEN WAYNE’S AND ZULEWSKI CLINICAL SCORES WITH THYROID DISORDERS - Sharma, Gaurav; Sharma, Garima; Sharma, Puneet; Lalitshrimali (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were to know the burden and spectrum of thyroid dysfunction in elderly population and to find out the relationship between Wayne’s and Zulewski clinical scores with thyroid disorders. Methods: This prospective cross-sectional study was conducted at tertiary care teaching hospital of Rajasthan only after approval from the Institutional Ethics Committee. The study participants consist of elderly patients of age 60 years and above. Wayne’s and Zulewski clinical score were used for the diagnosis of hypothyroidism and hyperthyroidism, respectively, and goiter was evaluated by the WHO classification. All the participants were subjected to biochemical test TSH and if required total T3, T4, thyroid antibody (Anti-TPO test), and USG/FNAC neck. Results: Total 165 patients were studied during the study period. The prevalence of thyroid disorders was 16.36%. The sensitivity of Zulewski clinical scores was 100% for both hypothyroid and overt hypothyroid patients, while the specificity was 58.39% and 54.72%, respectively, in cases of hypothyroidism and overt hypothyroid patients. The sensitivity of Wayne clinical scores for hyperthyroid was 33.33%, while specificity was 100%. Conclusions: The present study concluded that thyroid dysfunction is common among elderly and hypothyroidism is more common than hyperthyroidism. Clinically, we can suspect thyroid disorder, but, biochemically, thyroid function test is always being a gold standard to diagnose the disease.